Pengaruh Karakteristik CEO Terhadap Pengungkapan CSR Perusahaan Industri Keuangan Terdaftar di Bursa Efek Indonesia - Fatmawati, Anisa; Susanti, Elin Erlina (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze The purpose of this research is to examine the relationship between CSR and CEO Characteristics, Company Size, profitability, and leverage in financial companies. The data used is secondary data obtained from the public financial reports of the Indonesia Stock Exchange (IDX). Emitters on the IDX consist of 104 major financial companies from 2019 to 2023. The research sample is taken from 19 financials. This study uses panel data regression analysis, model testing, classical assumption testing, and hypothesis testing using the STATA 17 statistical software. The results of this study indicate that CEO age positively and significantly influences CSR disclosure